ANALISIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENUMBUHKAN KESADARAN KEBERSIHAN LINGKUNGAN MELALUI DIMENSI GOTONG ROYONG PADA SISWA KELAS IV DI SD NEGERI TEPISARI 02 - Putri Utami, Meisya Salma; Mahendra, Moefty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the process of implementation and the factors that influence the success of the Strengthening the Profile of Pancasila Students (P5) Project in fostering environmental cleanliness awareness through the dimension of mutual cooperation among 4th-grade students at SDN Tepisari 02. The research uses a qualitative approach with a descriptive design involving observation, interviews, and documentation. The results show that the P5 project at SDN Tepisari 02 was implemented as planned, with students actively participating in environmental cleanliness activities. The mutual cooperation activities, such as cleaning the school, sharing tasks, and maintaining cleanliness, successfully fostered a sense of environmental care and social responsibility. Additionally, this process reinforced the values of mutual cooperation among students, evident in their willingness to help and collaborate within groups. Teachers played a crucial role as facilitators, providing guidance and serving as role models. The study concludes that the implementation of P5 at this school is effective in promoting environmental awareness and mutual cooperation values among students, with strong school policy support and active student involvement.